BE PROUD OF INDONESIAN CULTURAL HERITAGE RICHNESS AND BE ALERT OF ITS PRESERVATION EFFORTS IN THE GLOBAL WORLD - Risda Asfina; Ririn Ovilia (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2016)
BANGGA DENGAN KEKAYAAN WARISAN BUDAYA INDONESIA DAN WASPADA DENGAN USAHA PELESTARIANNYA DI DUNIA GLOBALAbstractIndonesia as an archipelago country has a lot of cultural heritage that it is decently called as a multicultural country. The richness of Indonesian culture is not only in tangible cultural heritage but also in intangible one. It includes artifacts, inscriptions, traditional food, clothes, music instruments, oral traditions and expressions, performing arts, rituals and festive events, knowledge and practices concerning nature and the universe, and traditional craftsmanship. However, there have been a number of issues concerning the sustainability of Indonesian cultural heritage. Some of which are the difficulty of connecting culture with societies, the struggle to maintain inter-generational transfer of knowledge, lack of recognition, stylistic and thematic imitation, misappropriation by unauthorized reproduction or distribution, and foreign claims to Indonesian cultural heritage. Those issues are influenced by the globalization era in which the development of life style and technology increases rapidly. Due to the crucial value of the culture as the identity of a nation, therefore Indonesia surely needs to preserve it. This paper aims to discuss the richness of Indonesian culture, several cultural issues in global world, and the cultural heritage preservation efforts. The significance of this paper is to give a better understanding about these issues and to create awareness about the importance of maintaining cultural identity of the nation in global world. Keywords: Indonesian cultural heritage; preservation efforts; global worldAbstractIndonesia sebagai negara kepulauan memiliki banyak warisan budaya yang biasa dikenal sebagai negara multikultural. Kekayaan budaya Indonesia tidak hanya dalam warisan benda budaya tetapi juga dalam bentuk tak benda. Ini termasuk artefak, prasasti, makanan tradisional, pakaian, alat musik, tradisi dan ekspresi lisan, seni pertunjukan, ritual dan festival, pengetahuan dan praktek mengenai alam dan semesta, dan kriya tradisional. Namun, ada sejumlah isu mengenai keberlanjutan warisan budaya Indonesia. Beberapa di antaranya adalah kesulitan menghubungkan budaya dengan masyarakat, perjuangan untuk mempertahankan transfer pengetahun antar-generasi, kurangnya pengakuan, peniruan gaya dan tematik, penyalahgunaan reproduksi dan distribusi oleh pihak yang tidak sah, dan klaim asing untuk warisan budaya Indonesia. Isu-isu tersebut dipengaruhi oleh era globalisasi ketika perkembangan gaya hidup dan teknologi meningkat pesat. Mengingat pentingnya nilai budaya sebagai identitas suatu bangsa, bangsa Indonesia tentu perlu untuk melestarikannya. Tulisan ini bertujuan untuk membahas kekayaan budaya Indonesia, beberapa isu budaya di dunia global, dan upaya pelestarian warisan budaya. Signifikansi dari makalah ini adalah untuk memberikan pemahaman yang lebih baik tentang masalah ini dan untuk menciptakan kesadaran tentang pentingnya menjaga identitas budaya bangsa di dunia global.Keywords: warisan budaya Indonesia; usaha pelestraian; dunia global